2021
DOI: 10.1101/2021.03.09.434607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dual function monoclonal antibodies VIR-7831 and VIR-7832 demonstrate potent in vitro and in vivo activity against SARS-CoV-2

Abstract: VIR-7831 and VIR-7832 are dual action monoclonal antibodies (mAbs) targeting the spike glycoprotein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). VIR-7831 and VIR-7832 were derived from a parent antibody (S309) isolated from memory B cells of a 2003 severe acute respiratory syndrome coronavirus (SARS-CoV) survivor. Both mAbs contain an LS mutation in the Fc region to prolong serum half-life and potentially enhance distribution to the respiratory mucosa. In addition, VIR-7832 encodes an Fc G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
277
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 226 publications
(298 citation statements)
references
References 54 publications
16
277
2
3
Order By: Relevance
“…The auxiliary role of lectins in SARS-CoV-2 infection is in line with the known biology of these adhesion molecules that bind glycans characteristic of cellular membranes and pathogen surfaces to promote trans-infection 42 . Among the three auxiliary receptors, SIGLEC1 is of particular relevance because this receptor is prominently expressed in alveolar macrophages in association with viral RNA, thus supporting a model of trans-infection, tissue dissemination and the triggering of immune responses by myeloid cells, rather than a direct target for productive infection 43 . DC-SIGN and L-SIGN association with SARS-CoV-2 is also of relevance because of their interaction with blood endothelium and role in immune activation.…”
Section: Discussionmentioning
confidence: 91%
“…The auxiliary role of lectins in SARS-CoV-2 infection is in line with the known biology of these adhesion molecules that bind glycans characteristic of cellular membranes and pathogen surfaces to promote trans-infection 42 . Among the three auxiliary receptors, SIGLEC1 is of particular relevance because this receptor is prominently expressed in alveolar macrophages in association with viral RNA, thus supporting a model of trans-infection, tissue dissemination and the triggering of immune responses by myeloid cells, rather than a direct target for productive infection 43 . DC-SIGN and L-SIGN association with SARS-CoV-2 is also of relevance because of their interaction with blood endothelium and role in immune activation.…”
Section: Discussionmentioning
confidence: 91%
“…1) . Neutralization mediated by the casirivimab/imdevimab mAb cocktail (REGN10933 and REGN10987)( 14 , 15 ), which received an emergency use authorization in the US, and by VIR-7831 mAb( 10 , 38 ) (derivative of S309), which recently was shown to provide 85% protection against hospitalization and deaths in the COMET clinical trial, is unaffected by the L452R mutation. To address the role of B.1.427/B.1.429 L452R mutation in the neutralization escape from RBD-specific antibodies, we tested the binding of 35 RBD-specific mAbs to WT and L452R mutant RBD by biolayer interferometry ( Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Serum or plasma neutralizing activity is a correlate of protection against SARS-CoV-2 challenge in non-human primates( 39 , 40 ) and several monoclonal neutralizing Abs have demonstrated their ability to reduce viral burden as well as to decrease hospitalization and mortality in clinical trials( 10 , 14 , 15 , 22 , 38 , 41 ). The data presented here indicate that SARS-CoV-2 B.1.427/B.1.429 is associated with a reduction of sensitivity to plasma neutralizing Abs elicited by vaccination with two doses of Pfizer/BioNTech BNT162b2 or Moderna mRNA-1273 and by infection with the prototypic SARS-CoV-2 and the B.1.1.7 VOC.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, we subsequently demonstrated that, in vitro, sotrovimab retains activity against now widespread SARS-CoV-2 variants that were first identified in the United Kingdom (B.1.1.7), South Africa (B.1.351), Brazil (P.1), and California (B.1.427/B.1.429). 11,14,15 In contrast, many of the other monoclonal antibodies being developed for Covid-19 bind to the receptor-binding motif that engages the angiotensin-converting enzyme 2 (ACE2) receptor and is one of the most mutable and immunogenic regions of the virus; in some cases, these antibodies do not retain activity against the variants. [16][17][18][19] Sotrovimab contains a two-amino acid Fc modification (termed LS) to increase half-life and potentially improve bioavailability in the respiratory mucosa through enhanced engagement with the neonatal Fc receptor.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Sotrovimab has demonstrated potent effector functions in vitro, which have the potential to result in immune-mediated viral clearance. 13,14 Here, we report the results from a preplanned interim analysis of the COvid-19 Monoclonal antibody Efficacy Trial-Intent to Care Early (COMET-ICE) study evaluating the efficacy and safety of treatment with sotrovimab in high-risk, ambulatory patients with mild/moderate Covid-19. The trial is currently closed for enrollment; data collection is ongoing.…”
Section: Introductionmentioning
confidence: 99%